2021
DOI: 10.3389/fimmu.2021.697854
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in GVHD Therapy

Abstract: Graft versus host disease (GVHD) is a common complication and the leading cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Pharmacological immunosuppression used in GVHD prophylaxis and treatment lacks specificity and can increase the likelihood of infection and relapse. Regulatory T lymphocytes (Tregs) play a vital role in restraining excessive immune responses and inducing peripheral immune tolerance. In particular, clinical trials have demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 119 publications
0
31
0
Order By: Relevance
“…Several studies, mainly in reduced intensity conditioning HSCT for non-mailgnant diseases showed that alemtuzumab levels impact aGvHD, chimerism and lymphocyte recovery ( 59 , 60 ), but also in malignant diseases ( 61 ). Although alemtuzumab abrogated severe GvHD this was not necessarily associated with improved OS ( 62 ). In a study of 148 patients comparing alemtuzumab and ATG, alemtuzumab delayed T and natural killer cell recovery compared with ATG and overall and event-free survival were lower in patients who received alemtuzumab.…”
Section: Prophylaxis Of Gvhd In Different Settings Of Hsctmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, mainly in reduced intensity conditioning HSCT for non-mailgnant diseases showed that alemtuzumab levels impact aGvHD, chimerism and lymphocyte recovery ( 59 , 60 ), but also in malignant diseases ( 61 ). Although alemtuzumab abrogated severe GvHD this was not necessarily associated with improved OS ( 62 ). In a study of 148 patients comparing alemtuzumab and ATG, alemtuzumab delayed T and natural killer cell recovery compared with ATG and overall and event-free survival were lower in patients who received alemtuzumab.…”
Section: Prophylaxis Of Gvhd In Different Settings Of Hsctmentioning
confidence: 99%
“…Nonetheless, in this small, highly selected patient group, the rate of NRM was very high (50%). These deaths, mostly early post-transplant, were due to either regiment-related toxicity or infectious complications, indicating that despite accelerated immune recovery, this type of immune engineering still requires proof of clinical benefit ( 30 , 62 ). Another cell type with immunomodulatory activity are invariant natural killer T cells (iNKT), which secrete interleukin (IL)-4 and IL-10( 63 ).…”
Section: Prophylaxis Of Gvhd In Different Settings Of Hsctmentioning
confidence: 99%
“…Modulation of Tregs for therapeutic use has become an important area of investigation in GvHD, with the majority of studies focusing on in vitro-expanded polyclonal Tregs [ 75 , 76 , 77 , 78 ]. The first clinical trial of Tregs in GvHD showed modest impacts on acute GvHD symptoms but significant alleviation of the symptoms in chronic GvHD and reduction in the use of immunosuppressive agents [ 10 ].…”
Section: Application For Car Treg Therapymentioning
confidence: 99%
“…Despite this broad outline of Treg research in GVHD, many recent publications have already summarized the role of Tregs in GVHD in a detailed way (126)(127)(128), for which reason we will not go into further details at this point.…”
Section: Protective T Helper Cell Subsets In Gvhdmentioning
confidence: 99%